Importance and design of ventilation for an improved sleep quality - Çobanoğlu, Nur; Haktan Karadeniz, Ziya; Cemil Sofuoğlu, Sait; Toksoy, Macit (CLIMA 2022 conference, 2022)
Sleep quality, which significantly affects daily life, is also affected by indoor air quality as well as comfort aspects such as noise, temperature, and relative humidity in the sleeping environment. Carbon dioxide concentration is commonly considered as an indicator of indoor air quality, and it has been observed that increasing concentrations increase the number of awakenings resulting in lower sleep quality. In this study, ventilation flow rate is investigated specifically for bedroom and dormitory room dimensions as recommended by different countries to ensure that the carbon dioxide concentration in sleeping spaces is below an upper limit value (1000 ppm). The ventilation flow rate is evaluated by comparison to the methods recommended in ASHRAE standards (Ventilation Rate Procedure-VRP, Indoor Air Quality Procedure-IAQP and Natural Ventilation Procedure-NVP). Although VRP is widely used because a constant flow rate is recommended, which is an advantage due to design simplicity, it has been found to be insufficient for smaller sleeping space volumes and it gives higher values for larger volumes compared to the needed ventilation flow rates recommended by IAQP. Moreover, the fact that the flow rates calculated with VRP and IAQP overlap in a very narrow area shows that the use of VRP values for effective designs is limited. Consequently, we suggest that the system design should be operated with the IAQP and with demand-controlled ventilation, and an approach is offered to designers for direct use in practice.